Frailty as tested by the Liver Frailty Index in out-patient patients with cirrhosis in China: a cross-sectional study. Issue 4 (14th April 2023) - Siyu, Li; Yuan, Yuan; Ran, An; Minyan, Li
Abstract : Background: Early identification and prevention of frailty are very important for patients with cirrhosis. Methods: The study was the first to use Liver Frailty Index in out-patient patients with cirrhosis in China, and to analyze the influencing factors. Result: This study included 387 patients with cirrhosis. Frailty was diagnosed using the Liver Frailty Index. Multiple Logistic regression model were used to analyze influencing factors of frailty in out-patient patients with cirrhosis. Frailty was diagnosed in 9.6% of patients and prefrailty was diagnosed in 54.8% of patients. Age, sex, BMI, education level, monthly economic income, number of unplanned hospital admissions in the past year, cause of cirrhosis, Child-Pugh classification of cirrhosis, nutritional risk, physical activity, gait speed and Activity of Daily Living (ADL) Scale in the frailty, prefrailty and no frailty of groups were statistically significant. Age (OR, 1.103; CI, 0.064–0.132), BMI (OR, 0.817; CI, −0.302 to −0.104), education level (OR, 4.321; CI, 0.754–2.173), physical activity (OR, 3.580; CI, 0.534–2.016) and gait speed (OR, 0.001; CI, −8.188 to −4.972) were influential factors of frailty in out-patient patients with cirrhosis. Conclusion: Out-patient patients with cirrhosis have a high incidence of frailty and prefrailty. Elderly, reduced gait speed, no physical activity and low culture level are risk factors for frailty and prefrailty, and we should be identification and intervention early.